A STUDY OF ATTITUDE TOWARDS ICT OF PROSPECTIVE SECONDARY LEVEL TEACHERS IN RELATION TO THEIR GENDER AND ACADEMIC STREAMS - Khimnani , Priya; Rathore, Meenakshi (SCHOOL SCIENCE, 2018)
Use of ICT for teaching and learning has gathered a lot of attention in the past two decades. Innovation of computer technology as a learning tool can dramatically change the traditional concept of teaching. NCF 2005 emphasised the use of ICT in the classroom. NCFTE 2009 also emphasised the introduction of ICT training at both pre-service and inservice level. However, the teacher’s attitude is an important issue for integration of ICT in modern classroom teaching and learning process. The purpose of the present study is to find out the attitude of prospective secondary level teachers towards ICT with respect to their gender and academic streams (arts, science and commerce). Attitude scale towards information technology for teachers developed by Nasrin and Fatima Islahi was used to collect data from prospective secondary level teachers of Jodhpur. The scale measures four areas—Impact of IT, usefulness for students, productivity for teaching and teacher’s interest and acceptance. Results of the study will give us the direction in which our efforts are needed so as to effectively integrate ICT in school education as well as in higher education.